2018
DOI: 10.2217/fmb-2018-0135
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Listeria Monocytogenes Detection with a Dithiothreitol-Based Device During an Aseptic Hip Revision

Abstract: Prosthetic joint infection diagnosis is often difficult since biofilm-embedded microorganisms attach well to the prosthetic surfaces and resist their detection by conventional methods. DL-dithiothreitol has been described as a valid method for biofilm detachment on orthopedic devices. We report the case of an occasional detection of Listeria monocytogenes in a non immuno-compromised patient with a preoperative diagnosis of aseptic loosening. The infection diagnosis due to such rare bacteria was made postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…recently suggested that the duration of antibiotic therapy should be individualized [ 36 ]. In 18 patients (26.8%) one-stage revisions were applied and they were all asymptomatic over a 4-month to 3-year follow-up period with no recurrence [ 2 , 7 , 9 , 13 , 20 , 23 , 28 , 31 ]. All were acute cases, though two cases were chronic [ 9 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…recently suggested that the duration of antibiotic therapy should be individualized [ 36 ]. In 18 patients (26.8%) one-stage revisions were applied and they were all asymptomatic over a 4-month to 3-year follow-up period with no recurrence [ 2 , 7 , 9 , 13 , 20 , 23 , 28 , 31 ]. All were acute cases, though two cases were chronic [ 9 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…and Staph. E.) Two-stage revision Iv Amp for 4 days; po Amp for 3 mo Asymptomatic 2y later 26) 2012 [ 2 ] 34 [59] 34/43 (1992-2010 FNRCL) Age was 72 (range, 16–89)/61% M 79% (NS particularly for Arth/sty) 79% (NS particularly for Arth/sty) Hip 26 Knee 8 9y median time 12 one-stage revision 2two-stage revision 5 removal 13 no surgery 2 NS Primarily Amox 80% with Ami 48% for median duration 15w Asymptomatic 5 mo later 27) 2015 [ 5 ] 1 [60] 72/F Polymyalgia rheumatic Prednisone Knee 2y Debridement Iv Amp 6w; po Amox 6 mo Asymptomatic mo later 28) 2016 [ 6 ] 1 [61] 61/M DM; Cushing syndrome Prednisolonemg Fludrocortisone Knee 2y Debridement Iv Amp/ TMP/SMX 6w; po Amox/ TMP/S MX for 7 w Asymptomatic several months later 29) 2018 [ 13 ] 1 [62] 78/F Rectal cancer None Hip 21y One-stage revision with the diagnosis of aseptic loosening Van prophylaxis (Implant microbiological analysis LM) Asymptomatic 6 mo later 30) 2018 [ 3 ] 1[63] 69/M DM. Anemia, Hypertension None Knee 3w Debridement, mobile parts were replaced Iv Amox/2w folloed by TMP/SMX/10w Asymptomatic 1y later 31) 2019 [ 20 ] 1 [64] 50/M None None Hip 9 mo Debridement, mobile parts were replaced Iv Amp/Rif 13 d; po Lev/Fif for 3 mo Asymptomatic 20 mo later 32) 2...…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations